Spider wasps (Hymenoptera, Pompilidae) of the Republic of Khakassia, Eastern Siberia, Russia - Loktionov, V. M. (Zootaxa, 2022)
The spider wasp fauna of the Republic of Khakassia (Eastern Siberia, Russia) is revised. The number of species recorded from Khakassia has increased from 15 to 60, genera—from 4 to 17, subfamilies—from 2 to 3. An annotated list of the species with citation, examined material, and general distribution is given. The species, Anoplius piliventris (F. Morawitz), is newly recorded from Russia. Four genera, Agenioideus Ashmead, Anospilus Haupt, Aporinellus Banks, Tachyagetes Haupt, and 11 species are newly recorded from Eastern Siberia. One subfamily, 13 genera, and 45 species are recorded from Khakassia for the first time.